446 Accurate Localization of Back Pain by Radiomic Assessment of Sigma-1 Receptor Expression. (April 2023) - Haider, Ghani; Schonfeld, Ethan; Biswal, Sandip; Veeravagu, Anand
Abstract : INTRODUCTION: The current diagnostic tools that we have for back pain have low sensitivity and poor accuracy which leads to ineffective and unnecessary treatments, resulting in high health care costs and unwanted outcomes. Sigma-1 receptor (s1R) is broadly implicated in nociceptive signaling and peripheral pain sensation. METHODS: Specific patient selection for full body ([18F]FTC-146) PET/MRI scan was done after clinical and radiological review by a neurosurgeon specializing in spinal surgery. Six patients with various etiologies of back pain were included. For all the study participants, we recorded all relevant clinical details and reviewed prior diagnostic tests. All PET/MRI scans were completed at our institution's facilities and images were reviewed and correlated by a musculoskeletal radiologist to identify lesions that may be causing patient's symptoms. RESULTS: Our study results strongly support the likelihood of achieving enhanced diagnostic sensitivity to sources of back pain with the proposed s1r imaging approach. PET/MRI imaging matched the clinical diagnosis in all cases, including disc herniation, nerve compression, stenosis, and arthropathy. Additionally, it offered benefit over traditional MRI by identifying additional "functional" findings both within and outside the spine. This additional functional detail, was useful for patients with either no or multiple structural abnormalities on MRI to pinpoint the true cause of pain demonstrating the synergistic utility of this imaging modality. Such functional detail guided successful interventions including surgery, therapy, and injections in our patient cohort that successfully addressed the pain. CONCLUSIONS: Early results show promise for improved confidence and sensitivity in detecting sources of pain using full body ([18F]FTC-146) PET/MRI scan which can potentially improve patient management and outcomes.